Application of learning model with virtual lab and motivation in learning chemistry - Gulmah Sugiharti; Eva Rofinta Limbong (Pascasarjana Universitas Negeri Medan, 2018)
Abstract: This study aims to determine whether there is interaction between learning models and motivation to student learning outcomes. Samples were taken by purposive as much as 2 classes, experimental class I was treated with Problem Based Learning model using Virtual Lab and experiment II class was treated with PBL model using Real Lab on acid base titration material. Student learning outcomes data obtained using the test results of learning, while the data for motivation to learn through questionnaire motivation to learn. The data analysis technique uses two-way variance analysis and Fcount test. The results showed: 1) Hypothesis test obtained Fcount (A) and (B) equal to 18,551> Ftabel (0,05) (1,48) = 4,04 hence there is interaction between learning model using virtul lab and motivation learn to result learn chemistry of students. 2) Highly motivated students, taught by PBL model using Virtual Lab gives the highest average learning result (75,536 10,10), whereas taught by PBL model using real lab give average (75,2,43). 3) Students with low learning motivation, taught by PBL model using Virtual Lab give the average of learning result (71,59 10,74), whereas taught by PBL model using Real Lab give average (72,32 10,94). Thus it is concluded that there is an interaction between learning model and learning motivation toward chemistry learning result, and students who have high learning motivation are taught by PBL model using virtual lab give higher mean, whereas students who have low learning motivation are taught by PBL model using virtual lab provides a low average learning outcome.Keywords:learning outcomes, motivation, PBL model, virtual lab, real lab